Eruptive segmental collagenoma of the face in a young child: A rare case report (Journal of Fatima Jinnah Medical University, 2019)
Collagenomas are benign connective tissue dermal hamartomas of unknown etiology, characterized by an imbalance in the distribution and amount of collagen in the extracellular matrix. Very few cases are reported in children as most cases are seen in young adults. Case of a five years old girl is described, who presented with asymptomatic, skin colored infiltrated papules and plaques on the face with no systemic involvement diagnosed as eruptive collagenoma.
Keywords: Collagenoma; Hamartoma; Child; Face